(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Increased awareness of the multiple roles of RNA molecules has led to the realization that, in addition to their structural and functional roles, RNAs can be drug targets for small molecular therapy. Amikacin, a member of the aminoglycoside group of antibiotics, binds to specific sites in bacterial 16S ribosomal RNAs (rRNAs) and interferes with protein synthesis leading to cell death. Here, we used the systemic evolution of ligands by exponential enrichment (SELEX) method to isolate high affinity RNA fragments (aptamers) that bind to amikacin. After five rounds of SELEX selection, in which a linear N25 DNA template was used for the first selection cycle, the resulting RNA was cloned and sequenced. Among the 38 clones generated, five groups of sequences (groups A through E) containing nine conserved motifs were identified. The sequences of groups A and B were almost identical, indicating that the selected RNA was enriched. Subsequently, the Basic Local Alignment Search Tool program was used to search for the conserved motifs in bacterial 16S rRNA sequences. Strikingly, no sequence homology was observed, suggesting that the conserved sequences (motifs) identified in this studymay be novel target sites for amikacin. Bangladesh Pharmaceutical Journal 26(2): 134-143, 2023 (July)